PENINGKATAN KINERJA APARATUR DALAM MENUNJANG KUALITAS PELAYANAN PUBLIK DI BAGIAN SOSIAL SEKRETARIAT DAERAH KABUPATEN KUTAI BARAT - Lina Claudia (Jurnal Paradigma (JP), 2017)
The purpose of the research was to describe and analyze the improved performance of the apparatus in support of quality public service at the secretariat of the regional social west kutai regency. The result show that employee performance improvements made of the secretariat of the regional social west kutai regency, through improved knowledge, improved skills and expertise, employee formation update, and mutations work employees may work well, although there were still indications that the optimal yet thoroughly. Of the four sub focus research assigned turns out of provide enough appreciation of performance improvement officer, among others, improved education, provision of training opportunities, job formation update employees work and mutations work. Suboptimal performance improvement officers caused by mental and behavior of a fraction less employee-oriented performance improvements. The lack of opportunity given to employees in the following range of training because of the limited budget allocated for the development of the competence reform to support performance improvement officer.